Designing Knowledge Management for Legal Aspects to Enhance Governance of A Company in The Energy Sector (Case Study: PT KI) - Aditya Pramoda Ramadhan; Dedy Sushandoyo (Riviera Publishing, 2026)
Recently, the energy sector has experienced rapid growth in response to increasing global energy demand. Effective legal compliance is a key factor in achieving good corporate governance (GCG). To address this challenge, this study examined the current conditions and challenges of knowledge management in the legal function at PT KI, as well as explored how the implementation of knowledge management practices in legal processes could strengthen PT KI’s GCG. The research process involved problem identification, data collection through semi-structured interviews with company management, and analysis using several methods, including the People, Process, and Technology framework and SECI Analysis to evaluate the current state of knowledge management implementation at PT KI, as well as SWOT and TOWS analyses to identify areas for improvement. The objective was to understand the existing conditions at PT KI, particularly regarding the implementation of knowledge management within the legal function. The findings recommended the establishment of a Legal & Compliance Department and the development of comprehensive guidelines in the form of a framework and standard operating procedures (SOPs) based on the proposed business solution to implement knowledge management practices for the legal function and enhance PT KI’s corporate governance.